Digitization of retail as a factor of growth in consumer loyalty - I. V. Penkova; N. Yu. Voziyanova (Вестник Северо-Кавказского федерального университета)
Introduction. The deﬁning trend of modern business models is the active use of digital technologies, which create new opportunities for enterprises to operate in virtual markets and ensure increased consumer loyalty.Goal. Study of retail digitalization processes as a factor in increasing consumer loyalty.Materials and methods. The analysis was carried out on the basis of materials from scientiﬁc publications, analytical reports, statistical data using methods of analysis and synthesis, comparison and grouping, and statistical analysis.Results and discussion. The trends in the use of digital technologies in the practice of wholesale and retail trade enterprises have been studied. Key opportunities for using digital technologies to increase consumer loyalty have been identiﬁed. It has been established that technologies for collecting, processing and analyzing big data make it possible to study consumer preferences, frequency of purchases and “switching” conditions of consumers to ensure personalized interaction with a speciﬁc consumer; cloud services allow you to conduct data analytics in real time to make ﬂexible decisions and timely adaptation to changes in the market; digital platforms ensure increased communication interaction with consumers on the websites of online stores, marketplaces and social networks; artiﬁcial intelligence allows retailers to use data about customers and their behavior to create personalized marketing campaigns using not only search queries, but also computer vision.Conclusion. An analysis of the capabilities of digital technologies has shown that their use makes it possible to ensure: personalized consumer interaction with the company’s brand, the development of individualized loyalty programs, multi-channel communication, emotional satisfaction of consumers, which generally helps to increase consumer loyalty and the formation of a positive attitude towards the retailer’s brand.